Mechanism of Tonifying Spleen-lung Recipe in the Treatment of Chronic Bronchitis Based on Network Pharmacology and Observational Data - Wu, Hongjin; Li, Shenguang; Du, Xiaomei; Zhu, Kaigong; Li, Jing (Combinatorial Chemistry & High Throughput Screening, 2025)
BackgroundChronic bronchitis is a type of common chronic inflammatory respiratory disease, which is mainly characterized by chronic cough and expectoration. Clinical practice and experimental research have shown that the modified tonifying spleen-lung method has significant preventive and therapeutic effects on chronic lung diseases, but the mechanism of TSLR in the treatment of chronic bronchitis are not yet clear.ObjectiveTo explore the mechanism of tonifying spleen-lung recipe (TSLR) in the treatment of chronic bronchitis (CB) through network pharmacology combined with observational studies.Materials and MethodsThe effective components, core targets and signaling pathways of TSLR in the treatment of chronic bronchitis were obtained using network pharmacology. One hundred and thirty-seven elderly CB patients were selected as the observational group who were treated by TSLR, and 67 no-CB cases from the Physical Examination Center were selected as the control group. We compared the levels of inflammatory parameters between patients before and after TSLR treatment, and after treatment group with the control group were also compared.ResultsThe key effective components of TSLR selected by network pharmacology included quercetin, kaempferol, luteolin, and nobiletin, and the core targets involved HSP90AA1, AKT1, JUN, MAPK1, IL6, MAPK3, MAPK14, STAT1, NFKB1, and CDKN1. KEGG pathway enrichment analysis revealed that the TNF signaling pathway, PI3K-AKT and AGE-RAGE signaling pathways might play a key role in the treatment of CB. The observation study demonstrated that compared with the control group, the levels of WBC, NEU, NLR, PCT, and CRP in the research group after TSLR treatment were increased. Although the levels of WBC, NEU, NLR, and PCT in the research group after TSLR treatment were higher than those in the control group, the above indicators trend tended towards the control group, and there was no significant difference in CRP indicators between the control group and after treatment group.ConclusionTSLR had a good therapeutic effect on chronic bronchitis patients, which might be related to the fact that the natural active components in TSLR inhibit inflammation by regulating the expression of proteins related to PI3K-AKT and TNF signaling pathways.
Keywords: clinical research